The Important Role Of Green HRM In Employee Green Behavior And Organizational Green Performance - Anwar, Mohammad Ziad; L Jatmiko Jati; Ika Yuliana; Rizal Ramdani; Restu Alpiansah (Jurnal Ekonomi, 2024)
Academics and researchers in Indonesia still rarely carry out comprehensive and in-depth studies regarding the influence of implementing green HRM on green performance and green behavior. The main emphasis of scientific investigations and inquiry in Indonesia is related to the direct consequences of implementing green HRM on organizational green performance. The purpose of this investigation is to empirically examine how green behaviour of employees and green HRM influence organisational green performance. This research involved 144 workers employed by SMEs in Indonesia. This research is a quantitative research category using Partial Least Squares (PLS) statistical techniques and a questionnaire-based survey approach. This research finds that the application of green HRM has a significant effect on green behavior and organizational green performance. Furthermore, this research finds that employee green behavior moderates the influence of green HRM on organizational green performance. Especially in the fields of human resources and organizational management, we hope that the results of this research can significantly advance green theory. In addition, the research results can be used as an alternative strategy to improve organizational environmental sustainability.